Analisis Biaya Penyelenggaraan Pendidikan di Madrasah Tsanawiyah Negeri (MTsN) - H. M. Djumransjah (Universitas Negeri Malang, 2016)
This study was focused on educational costs in the Madrasah Tsanawiyah Negeri (MTsN). The data were gathered in Madrasah Tsanawiyah Negeri (MTsN) Malang I by using documents and interviews, and then analyzed by a reflective approach. The results indicated that the average cost was Rp.510,443.00 per-annum/student. The budget was spent on daily operation (40.46%), maintenance (28.98%), staff honoraria (28.31%), and teaching aids or educational media (2.07%). The fund comes from central government through developmental fund (DIP) and from Parent Association (BP3) through educational support (SPP), infaq, zakat, etc